2003
DOI: 10.1002/chin.200348273
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products — A Simple Model to Explain Chemical Diversity

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
71
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 1 publication
1
71
1
2
Order By: Relevance
“…Ecologists struggle to understand not only the consequences of diversity loss but also how to quantify ecologically relevant dimensions of diversity, including genetic, taxonomic, and functional diversity. Although it has been difficult to measure, phytochemical diversity (i.e., richness and abundance of plant compounds) is a key axis of functional diversity (1) that affects associated trophic levels and is likely driving other aspects of biodiversity (2)(3)(4). Variation in phytochemical or metabolic diversity in plants, which is further downstream than genomic, transcriptomic, or proteomic diversity (5,6), potentially reflects variation in response to a diversity of natural enemies, including specialist and generalist insect herbivores (7,8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ecologists struggle to understand not only the consequences of diversity loss but also how to quantify ecologically relevant dimensions of diversity, including genetic, taxonomic, and functional diversity. Although it has been difficult to measure, phytochemical diversity (i.e., richness and abundance of plant compounds) is a key axis of functional diversity (1) that affects associated trophic levels and is likely driving other aspects of biodiversity (2)(3)(4). Variation in phytochemical or metabolic diversity in plants, which is further downstream than genomic, transcriptomic, or proteomic diversity (5,6), potentially reflects variation in response to a diversity of natural enemies, including specialist and generalist insect herbivores (7,8).…”
mentioning
confidence: 99%
“…From a coevolutionary perspective, the concept of an arms race between plants and herbivores, yielding increasing diversity of plant secondary compounds (3), has long been an appealing theoretical framework for evolutionary biologists, and is still a theoretical cornerstone of chemical ecology (Table 1). Additionally, the screening hypothesis, which has received less attention, suggests that phytochemical diversity is maintained because it increases a plant's likelihood of containing a potent compound or a precursor to a potent compound that is effective against a particular type of natural enemy, cumulatively creating a selective advantage against a diverse assemblage of natural enemies (2). The screening hypothesis also posits that phytochemical diversity provides effective combinations of compounds that work synergistically against a particular type of natural enemy (10,11).…”
mentioning
confidence: 99%
“…The extensive structural and functional diversity of natural polyketides may be the result of an interspecies and host-pathogen chemical "arms race". Alternatively, the ability to generate chemical diversity might be an end in itself, increasing the likelihood of discovering biologically potent molecules (4).…”
mentioning
confidence: 99%
“…The quest to exploit factors leading to the production of diverse molecular structures from cultured microorganisms represents a continuing challenge for natural products research (Firn and Jones, 2003) Filter-feeding marine invertebrates, such as sponges, have been shown to host a variety of microorganisms that do not merely reflect the microbial communities present in the surrounding seawater but appear to constitute a more specialized association between sponge hosts and microbial associates (Friedrich et al, 1999). An early, conservative estimate based upon thousands of assayed sponge species suggested that as many as 11% produce cytotoxic compounds (Garson, 1994).…”
Section: Introductionmentioning
confidence: 99%